El marketing interno como aliado estratégico en la gestión de recursos humanos de la empresa Entel, Iquitos 2022 - Concha Rengifo, Altair Emilio (2023)
The objective of this research was to determine the relationship between internal marketing with the human resources management of the company Entel, Iquitos 2022, the type of quantitative level research, non-experimental design, descriptive and correlational type was used. The population is made up of all employees of the Entel company in the city of Iquitos, the survey was conducted on a total of 20 people, the result was that with a Pearson correlation value equal to 0.906** and the sigma value (bilateral) which is 0.000, we conclude that there is a significant relationship between internal marketing and human resource management, in the company Entel, Iquitos 2022. After analyzing the dimensions of the variables and according to the response of more than 50% We conclude that both the internal marketing variable and the human resource management variable have a medium level and require significant improvements. The investigation concluded that there is a significant relationship between internal marketing and human resource management, in the company Entel, Iquitos 2022.